2021
DOI: 10.1002/adtp.202100087
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small Anti‐ACE2 Peptides to Inhibit SARS‐CoV‐2 Infectivity

Abstract: COVID‐19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which infects host cells by binding its viral spike protein receptor‐binding domain (RBD) to the angiotensin converting enzyme 2 (ACE2) on host cells. Blocking the SARS‐CoV‐2‐RBD/ACE2 interaction is, therefore, a potential strategy to inhibit viral infections. Using a novel biopanning strategy, a small anti‐ACE2 peptide is discovered, which shows high affinity and specificity to human ACE2. It blocks not only the SARS‐CoV‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] ...…”
Section: Uncited Referencesunclassified
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] ...…”
Section: Uncited Referencesunclassified
“…Smaller size proteins have several advantages as in reduced production costs with high output, low side effects, high selectivity, etc. [ 35 , 36 ]. Cao et al identified LCB1 as a smaller miniprotein with 56 AAs [ 20 ], but it is still considered to be a large inhibitor [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A series of concentrations of each miniprotein (0.1, 1, 10, 50, 100, 200, 500, and 1000 nM) will be analyzed to calculate the equilibrium dissociation constant (K D ) values. Next, we will select the miniproteins that exhibit high affinity to SARS-CoV-2 RBD and study whether they can block the SARS-CoV-2 RBD/ACE2 interaction as we reported [ 35 ]. A 96-well plate will be coated with SARS-CoV-2 RBD protein, blocked with bovine serum albumin (BSA), and incubated with the miniproteins at room temperature for 1 h. After washing, biotinylated-ACE2 protein will be added to the wells and incubated for 1 h. Streptavidin-HRP and substrate will be finally added to measure absorbance at 450 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that many out of 26 analyzed peptides signifi cantly aff ected the biological activity of the recombinant human ACE2. However, the peptide CPS4 (NNYLWWMTEYHD) and its dimer eff ectively blocked virus entry into the cell, but did not aff ect the functional activity of ACE2 [93]. It should be mentioned that no results on the in vivo activity have been reported for any of the discussed peptides (Table 2).…”
Section: Prophylactics and Therapy Of Sars-cov-2 Infection Molecular ...mentioning
confidence: 99%